Salt stress in the early development stage of peanut genotypes - Lessa, Carla Ingryd Nojosa; Sousa, Geocleber Gomes de; Sousa, Henderson Castelo; Pereira Filho, João Valdenor; Goes, Geovana Ferreira (Revista de Ciências Agroveterinárias, 2022)
Salt stress impairs the early development of the peanut crop. However, the intensity of its effects depends on other factors, such as species or cultivar. The objective of this study has been to evaluate the effects of salt stress on the early growth of peanut genotypes. The experiment was carried out in an agricultural greenhouse under pot conditions at the University for International Integration of the Afro-Brazilian Lusophony in Redenção/CE/Brazil. The treatments were: two levels of electrical conductivity of the irrigation water (2.0 and 5.0 dS m-1) and five peanut genotypes (cultivar BR-1, Accession 08, 28, 43, and 130). They were implemented in a factorial design (2 × 5) under a completely randomized design with five replications. The following variables were evaluated at 34 days after sowing: number of leaves, plant height, leaf area, stem diameter, shoot dry mass, electrical conductivity of the saturated soil extract, and pH. Irrigation water with a conductivity of 5.0 dS m-1 reduced leaf area, plant height, stem diameter, number of leaves, and shoot dry matter of the peanut genotypes cultivar BR-1, Accessions 08, 28, 43, and 130. It also raised the pH and electrical conductivity of the saturated soil extract in relation to the water with lower conductivity (2.0 dS m-1).